Validation of modernized questionnaire MSAQ in patients with coronary artery disease metabolic syndrome, having had percutaneous coronary intervention for acute coronary syndrome without persistent elevation of ST segment - Leonid Semenovich Kholopov; Natalia Vladimirovna Chumachenko; Iryna Alexandrovna Sydorenko (Journal of Education, Health and Sport, 2016)
Kholopov Leonid, Chumachenko Natalia, Sydorenko Iryna. Validation of modernized questionnaire MSAQ in patients with coronary artery disease metabolic syndrome, having had percutaneous coronary intervention for acute coronary syndrome without persistent elevation of ST segment. Journal of Education, Health and Sport. 2016;6(1):171-178. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.45171